Ameliorated or Acquired Cytostatic/Cytotoxic Properties of Nucleosides by Lipophilization. Issue 12 (December 2015) - Knies, Christine; Bonaterra, Gabriel; Hammerbacher, Katharina; Cordes, Andrea; Kinscherf, Ralf; Rosemeyer, Helmut
Abstract: A series of nucleolipids, containing one of the β ‐D ‐ribonucleosides 5‐fluorouridine, 6‐azauridine, uridine, or 5‐methyluridine were lipophilized, either at the O ‐2′, 3′‐position and/or at N(3) of the nucleobase with a large variety of hydrophobic residues. The resulting nucleolipids as well as the parent nucleosides and the lipid precursors were investigated in vitro with respect to their antitumor activity towards i ) ten human tumor cell lines from the NCI 60 panel and ii ) partly against three further tumor cell lines, namely a ) human astrocytoma/oligodendro glioma GOs‐3, b ) rat malignantneuroectodermal BT4Ca, and c ) differentiated human THP‐1 macrophages. Inspection of the doseresponse curves allows two main conclusions concerning lipid determinants lending the corresponding nucleoside an ameliorated or an acquired antitumor activity: i ) introduction of either a symmetrical O ‐2′, 3′‐nonadecylidene ketal group or introduction of an O ‐2′, 3′‐ethyl levulinate moiety plus an N(3)‐farnesyl group leads often to nucleolipids with significant cytostatic/cytotoxic properties; ii ) for the two canonical and non‐toxic nucleosides uridine and 5‐methyluridine, the condensation with also non‐toxic lipids gives nucleolipids with a pronounced antitumor activity. Abstract :